THE IMPACT OF RISK MANAGEMENT STRATEGY IN BUSINESS RESILIENCE: A CASE IN COFFEE BEDA - Aryandi Akbar; Frank Gruben; Agung Juliarto (Diponegoro Journal of Accounting, 2023)
As the public's interest in coffee shops grows, numerous new entrepreneurs enter the market. As a result, having a risk management strategy as an instrument to prevent or even eliminate uncertainty is necessary, especially for a new business. This study aims to ensure that many Indonesian coffee shops take adequate steps to be resilient in the face of this chaotic pandemic, while also recognizing the Management Risk. An interview and a literature review will be conducted as part of this project. According to the findings, many Indonesian coffee shops are unaware of the significance of establishing a risk management strategy in order to be resilient.